Assessing the fate and impact of ciprofloxacin on bacterial community in activated sludge process - Chan, Joey (2017)
The study of emerging contaminants (ECs) has recently been emphasized due to their adverse effects on natural microbial processes (e.g., nutrient regeneration and pollutant degradation) and human health. ECs are highly recalcitrant and toxic even at very low concentrations (ng/L to µg/L). One of the ECs of interest is ciprofloxacin (CIP), which is the most widely prescribed fluoroquinolone antibiotic for the treatment of bacterial infections. It has been found that majority of CIP ingested exits the human body unmetabolized via faeces and urine thus resulting in large amounts being directed into wastewater treatment plants (WWTPs). There are studies available on biodegradation of CIP in water and soil and its impacts on soil microbial activities. However, little is known about its fate (degradation, biotransformation and adsorption) and its impacts during wastewater treatment processes. The aim of this project is to examine the fate of CIP and the impact on microbial communities with prolonged exposure of CIP-enriched feed at 50 µg/L and 500 µg/L. An aerobic bioreactor was seeded with activated sludge from Jurong Water Reclamation Plant. The biodegradation/biotransformation and adsorption of CIP was elucidated by measuring its concentration in sludge and effluent using high performance liquid chromatography (HPLC). COD removal at each concentration remained stable at high removal rates showing that the tested concentrations have no impact on microbial degradation. However, CIP removal remained low at about 20% (Cycle 4, 8, 12, 16 and 20). Ultrasonic solvent extraction and mass balance analysis was used to determine the fate of CIP after every cycle at selected intervals. Up to 21% of CIP was biodegraded during the activated sludge process. MIC tests were conducted to test for resistance towards CIP after prolonged exposure. However, as CIP is an antibiotic and is toxic to numerous bacteria, only a slight increase in MIC was observed after 16 cycles. The results of this project will have important implications in the study of development of antibiotic resistance as well as the development of sustainable engineering strategies such as better optimisation of the conditions during activated sludge treatment resulting in better management of ECs in the environment.